2003
DOI: 10.1038/sj.ijir.3900942
|View full text |Cite
|
Sign up to set email alerts
|

Inflatable penile prosthesis: site-specific malfunction analysis

Abstract: The purpose of this study was to analyze retrospectively the exact site(s) of device failure of a large series of Mentor Alpha I inflatable penile prostheses. The study consisted of 442 patients implanted over a 12-year period. Only those patients who developed a device malfunction and returned for re-evaluation by the author were included. The exact site(s) of device malfunction were obtained from a review of operative reports. The average length of follow-up in this series was 63 months, ranging from 1 to 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Debocq and colleagues reported that the Alpha I IPP had a 96% cumulative proportional survival at 63 months, versus an 84% CPS for the Ultrex and CX models [28]. The author of this review carried out a site-specific malfunction analysis for a series of 442 Alpha I IPPs; the most frequent site of malfunction was at the junction of the silicone tubing with the pump strain reliefs [29].…”
Section: Inflatable Penile Prosthesis Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Debocq and colleagues reported that the Alpha I IPP had a 96% cumulative proportional survival at 63 months, versus an 84% CPS for the Ultrex and CX models [28]. The author of this review carried out a site-specific malfunction analysis for a series of 442 Alpha I IPPs; the most frequent site of malfunction was at the junction of the silicone tubing with the pump strain reliefs [29].…”
Section: Inflatable Penile Prosthesis Resultsmentioning
confidence: 97%
“…The most common sites of device failure in this author's series are the junctions of the silicone tubing with the strain reliefs (reinforced areas where the silicone tubing is attached to the pump) [29]. Other authors have also noticed this propensity [30].…”
Section: Inflatable Penile Prosthesis Complicationsmentioning
confidence: 97%
“…This has been described previously as the weakest part of the Mentor Alpha-1 IPP [7,8]. The Mentor Corporation has tried to solve this problem by releasing a new model that has been strengthened at this site [8].…”
Section: Discussionmentioning
confidence: 95%
“…Garber et al looked at 442 cases and found that 5.0% developed device malfunction, with the majority of device failure occurring at 48-59 months. 9 Their study design was to determine the site of mechanical failure, which demonstrated that half of their scrotal implants malfunctioned at the junction where the tubing and the pump strain relief of the Mentor Alpha I meet.…”
Section: Discussionmentioning
confidence: 99%